Identification of ArgP and Lrp as transcriptional regulators of lysP, the gene encoding the specific lysine permease of Escherichia coli - Ruiz, Jimena (2011)
Expression of lysP, which encodes the lysine-specific transporter LysP in Escherichia coli, is regulated by the concentration of exogenous available lysine. In this study, the LysR-type transcriptional regulator ArgP was identified as the activator of lysP expression. At lysine concentrations higher than 25 μM, lysP expression was shut off and phenocopied an argP deletion mutant. Purified ArgP-His 6 bound to the lysP promoter/control region at a sequence containing a conserved T-N 11-A motif. Its affinity increased in the presence of lysine but not in the presence of the other known coeffector, arginine. In vivo data suggest that lysine-loaded ArgP and arginine-loaded ArgP compete at the lysP promoter. We propose that lysine-loaded ArgP prevents lysP transcription at the promoter clearance step, as described for the lysine-dependent regulation of argO (R. S. Laishram and J. Gowrishankar, Genes Dev. 21:1258-1272, 2007). The global regulator Lrp also bound to the lysP promoter/control region. An lrp mutant exhibited reduced lysP expression in the absence of external lysine. These results indicate that ArgP is a major regulator of lysP expression but that Lrp modulates lysP transcription under lysine-limiting conditions. © 2011, American Society for Microbiology.